A hot-spot energy indicator for welded plate connections under cyclic axial loading and bending. (15th September 2017) - Feng, Liuyang; Qian, Xudong
Highlights: The paper presents a volume-based hot-spot energy approach. The volume-based energy incorporates the stress gradients near the weld toe. The energy approach leads to enhanced correlations for existing fatigue test data. Abstract: The stress gradient near the weld toe caused by both the geometry and loading conditions can lead to significant scatters in the fatigue life of welded plate joints, driven by the same nominal or structural stress. This study proposes a volume-based hot-spot energy indicator near the weld toe to incorporate the stress gradients along both the surface and thickness directions for a wide range of plate thickness and different loading conditions. The comparison against reported experimental data validates the proposed volume-based hot-spot energy indicator, which reduces the scatter in the high-cycle fatigue lives of welded plate joints compared to the existing structural stress methods. To facilitate engineering applications, this study develops an analytical formulation to estimate the hot-spot energy indicator based on the notch stress intensity factors and Williams' solution.